Evaluating aminophylline and progesterone combination treatment to modulate contractility and labor‐related proteins in pregnant human myometrial tissues - Pei F. Lai; Roger C. Young; Rachel M. Tribe; Mark R. Johnson (Wiley, 2021)
Abstract Progesterone (P4) and cyclic adenosine monophosphate (cAMP) are regarded as pro‐quiescent factors that suppress uterine contractions during pregnancy. We previously used human primary cells in vitro and mice in vivo to demonstrate that simultaneously enhancing myometrial P4 and cAMP levels may reduce inflammation‐associated preterm labor. Here, we assessed whether aminophylline (Ami; phosphodiesterase inhibitor) and P4 can reduce myometrial contractility and contraction‐associated proteins (CAPs) better together than individually; both agents are clinically used drugs. Myometrial tissues from pregnant non‐laboring women were treated ex vivo with Ami acutely (while spontaneous contracting) or throughout 24‐h tissue culture (±P4); isometric tension measurements, PKA assays, and Western blotting were used to assess tissue contractility, cAMP action, and inflammation. Acute (1 h) treatment with 250 and 750 μM Ami reduced contractions by 50% and 84%, respectively, which was not associated with a directly proportional increase in whole tissue PKA activity. Sustained myometrial relaxation was observed during 24‐h tissue culture with 750 μM Ami, which did not require P4 nor reduce CAPs. COX‐2 protein can be reduced by 300 nM P4 but this did not equate to myometrial relaxation. Ami (250 μM) and P4 (100 and 300 nM) co‐treatment did not prevent oxytocin‐augmented contractions nor reduce CAPs during interleukin‐1β stimulation. Overall, Ami and P4 co‐treatment did not suppress myometrial contractions more than either agent alone, which may be attributed to low specificity and efficacy of Ami; cAMP and P4 action at in utero neighboring reproductive tissues during pregnancy should also be considered.